The effects of rhythmic auditory stimulation on functional ambulation after stroke: a systematic review - Samira Gonzalez-Hoelling; Gloria Reig-García; Carme Bertran-Noguer; Rosa Suñer-Soler (BMC, 2024)
Abstract Background Several studies have reported the effect of rhythmic auditory stimulation (RAS) on functional ambulation in stroke patients, yet no systematic overview has yet been published. This study aims to synthesize the available evidence describing changes in stroke patients after RAS intervention for functional ambulation and the use of walking assistive devices, and to find out if the effect of RAS and music-based RAS differs depending on the lesioned area. Methods The PubMed, PEDro, Cochrane Central Register of Controlled Trials, Web of Science, Scopus and CINAHL electronic databases were searched for reports evaluating the effect of RAS on walking in stroke patients, applying the PICOS criteria for the inclusion of studies. Results Twenty one articles were included (948 stroke survivors). Most studies were of good methodological quality according to the PEDro scale, but they had a high risk of bias. The most consistent finding was that RAS improves walking and balance parameters in stroke patients in all phases compared to baseline and versus control groups with conventional treatment. Functional ambulation and the use of walking assistive devices were inconsistently reported. Several studies also suggest that RAS may be as good as other complementary therapies (horse-riding and visual cueing). Conclusions Despite the beneficial effects of RAS, the question remains as to whether it is better than other complementary therapies. Given the heterogeneity of the interventions, the interventions in control groups, the varied durations, and the different outcome measures, we suggest that care should be taken in interpreting and generalizing findings. PROSPERO Registration CRD42021277940.